Planning and Scheduling in Manufacturing and Services - Pinedo, Michael L.; SpringerLink (Online service) (New York, NY : Springer New York, 2005)
This book focuses on planning and scheduling applications. Planning and scheduling are forms of decision-making that play an important role in most manufacturing and services industries. The planning and scheduling functions in a company typically use analytical techniques and heuristic methods to allocate its limited resources to the activities that have to be done. The application areas considered in this book are divided into manufacturing applications and services applications. The book covers five areas in manufacturing: project scheduling, job shop scheduling, scheduling of flexible assembly systems, economic lot scheduling, and planning and scheduling in supply chains. It covers four areas in services: reservations and timetabling, tournament scheduling, planning and scheduling in transportation, and workforce scheduling. At the end of each chapter, a case study or a system implementation is described in detail. Numerous examples and exercises throughout the book illustrate the material presented. The fundamentals concerning the methodologies used in the application chapters are covered in the appendices. This book is suitable for more advanced students in industrial engineering and operations research as well as graduate students in business. Michael Pinedo is the Julius Schlesinger Professor of Operations Management in the Stern School of Business at New York University. His research interests lie in the theoretical and applied aspects of planning and scheduling. He has written numerous papers on the theory of deterministic and stochastic scheduling and has also consulted extensively in industry. He has been actively involved in the development of several large industrial planning and scheduling systems.
Preliminaries -- Manufacturing Models -- Service Models -- Planning and Scheduling in Manufacturing -- Project Planning and Scheduling -- Machine Scheduling and Job Shop Scheduling -- Scheduling of Flexible Assembly Systems -- Economic Lot Scheduling -- Planning and Scheduling in Supply Chains -- Planning and Scheduling in Services -- Interval Scheduling, Reservations, and Timetabling -- Scheduling and Timetabling in Sports and Entertainment -- Planning, Scheduling, and Timetabling in Transportation -- Workforce Scheduling -- Systems Development and Implementation -- Systems Design and Implementation -- Advanced Concepts in Systems Design -- What Lies Ahead?.
Keywords: Mathematics; Business; Management science; Organization; Planning; Production management; Applied mathematics; Engineering mathematics; Operations research; Mathematics; Operations Research, Management Science; Operations Management; Organization; Business and Management, general; Applications of Mathematics; Electronic books